A Sistem Informasi Desa Terintegrasi Kekayaan Alam Di Desa Lakatong Kabupaten Takalar - Hamdi, Fauzan (MALLOMO: Journal of Community Service, 2024)
Community service activity entitled Integrated Village Information System for Natural Wealth in Lakatong Village, Takalar Regency. The aim of this activity is to provide training on integrated village information systems. The implementation method for community service activities consists of several stages, starting from coordination meetings, procurement of materials, tools and supporting facilities, implementation of training activities, as well as program evaluation and monitoring. The targets of this community service activity are the Lakatong Village government and village officials, the Lakatong village community, especially members of the I Malla Langngi Youth Organization, Barombong District. The expected output result from this activity are expected to increase abilities, skills and creativity in improving services to the community, be able to process government databases based on information technology, and be able to process and optimize the Lakatong Village government website.